Sovereignty : Moral and Historical Perspectives - Johnson, James Turner (Book collections on Project MUSE., 2014)
Sovereignty generally refers to a particular national territory, the inviolability of the nation's borders, and the right of that nation to protect its borders and ensure internal stability. From the Middle Ages until well into the Modern Period, however, another concept of sovereignty held sway: responsibility for the common good. James Turner Johnson argues that these two conceptions -- sovereignty as self-defense and sovereignty as acting on behalf of the common good -- are in conflict and suggests that international bodies must acknowledge this tension. Johnson explores this earlier concept of sovereignty as moral responsibility in its historical development and expands the concept to the current idea of the Responsibility to Protect. He explores the use of military force in contemporary conflicts, includes a review of radical Islam, and provides a corrective to the idea of sovereignty as territorial integrity in the context of questions regarding humanitarian intervention. Johnson's new synthesis of sovereignty deepens the possibilities for cross-cultural dialogue on the goods of politics and the use of military force.